Unraveling the metabolic pathways between atherosclerosis and sarcopenia - Yu, Mei; Ge, Lichao; Fu, Chen; Zhao, Rujia (Frontiers in Endocrinology, 2026)
Sarcopenia and atherosclerosis are age-related conditions pathologically intertwined through a self-reinforcing, bidirectional cycle. This review dissects the core mechanistic pillars of this synergy such as insulin resistance, chronic low-grade inflammation, ectopic lipid deposition, and hormonal dysregulation. We detail how skeletal muscle dysfunction exacerbates systemic insulin resistance and inflammatory cascades that accelerate endothelial damage and atherogenesis. Conversely, atherosclerotic vascular impairment compromises microcirculatory function, inducing muscle ischemia and metabolic decline. Beyond pathogenesis, we evaluate integrated intervention, including combined exercise, anti-inflammatory diets, and pleiotropic pharmacotherapies, that concurrently target shared pathways in muscle and vasculature. By framing this comorbidity within the context of aging hallmarks, we advocate a paradigm shift from organ-specific management toward a holistic, geroscience-based approach to mitigate frailty and disability in the aging population.